Role of C/EBP-β in Methamphetamine-Mediated Microglial Apoptosis - Chen, Xuebing; Lu, Jiancong; Zhao, Xu; Chen, Chuanxiang; Qiao, Dongfang; Wang, Huijun; Yue, Xia (Frontiers in Cellular Neuroscience, 2019)
Methamphetamine (MA) is a widely abused psychoactive drug that primarily damages the nervous system. However, the involvement of MA in the survival of microglia remains poorly understood. CCAAT-enhancer binding protein (C/EBP-β) is a transcription factor and an important regulator of cell apoptosis. Lipocalin2 (lcn2) is a known apoptosis inducer and is involved in many cell death processes. We hypothesized that C/EBP-β is involved in MA-induced lcn2-mediated microglial apoptosis. To test this hypothesis, we measured the protein expression of C/EBP-β after MA treatment and evaluated the effects of silencing C/EBP-β or lcn2 on MA-induced apoptosis in BV-2 cells and the mouse striatum after intrastriatal MA injection. MA exposure increased the expression of C/EBP-β and stimulated the lcn2-mediated modulation of apoptosis. Moreover, silencing the C/EBP-β-dependent lcn2 upregulation reversed the MA-induced microglial apoptosis. The in vivo relevance of these findings was confirmed in mouse models, which demonstrated that the microinjection of anti-C/EBP-β into the striatum ameliorated the MA-induced decrease survival of microglia. These findings provide a new insight regarding the specific contributions of C/EBP-β-lcn2 to microglial survival in the context of MA abuse.